Atuação escolar e processos autolesivos na adolescência: a percepção dos professores sobre este fenômeno - Silva, Wesley Júnior (2023)
This master’s thesis discusses, based on two complementary articles, the school performance towards the cases of self-injury in adolescence, as from an empirical research developed with teachers who worked in brazilian public schools. The investigation is justified due to the occurrence of self-injury in adolescents and the Federal Law 13.819/2019 publication, that institutes in Brazil the "National Policy for the Prevention of Self-injury and Suicide", including the school as one of the agents responsible for the mandatory notification of violence, such as self-directed violence caused by students. The first article that makes up this study is about how teachers, in elementary school and high school, identify self-inflicted violence by students and the actions they take when faced with such practices. An online questionnaire was applied, and the answers were analyzed using descriptive statistics. The second article investigated how elementary and high school teachers identify the occurrence of self-injury in students and their conceptions about the role of the teacher and the school in these situations. Interviews were conducted with four teachers using a semi-structured script, and the transcripts were treated using the thematic content analysis method. Most of the teachers were between 32 and 40 years old, had been teaching for 6 to 15 years and at least two years at the school researched. All declared that they did not feel prepared to deal with cases of self-injury, reporting a lack of training and information material; of these, eight teachers have already taught to a student who practiced self-injury, and this action is often informed by another person and not directly perceived by the teacher. It was observed that, according to teachers, self-injuries begin with the advent of adolescence in students, and there are several causes and student behaviors that allow identification, in addition to information provided by other students and school professionals. The participants do not feel prepared to deal with the issue, but they believe they have a very important role, as does the school, which should provide an attentive look and become welcoming to adolescents. When observing behaviors such as sudden mood swings, ora drop in school performance, teachers can offer attention and shelter, and also, when noticing that the case is serious, they can call the multidisciplinary team, tell the parents and/or guardians, and notify the municipal adolescent protection agency.